Evidence for the Rapid and Divergent Evolution of Mycoplasmas: Structural and Phylogenetic Analysis of Enolases - Chen, Rong; Zhao, Lin; Gan, Rong; Feng, Zhixin; Cui, Chenxi; Xie, Xing; Hao, Fei; Zhang, Zhenzhen; Wang, Li; Ran, Tingting; Wang, Weiwu; Zhang, Shuijun; et al. (Frontiers in Molecular Biosciences, 2022)
Mycoplasmas are a group of prokaryotes without cell walls that have evolved through several rounds of degenerative evolution. With a low cell DNA G+C content and definitively long genetic lineages, mycoplasmas are thought to be in a state of rapid evolution. However, little associated evidence has been provided. Enolase is a key enzyme in glycolysis that is widely found in all species from the three domains, and it is evolutionarily conserved. In our previous studies, enolase acted as a virulence factor and participated in cell-surface adhesion in Mycoplasma hyopneumoniae. Furthermore, unique loop regions were first found in the crystal structure of Mhp Eno. Here, enolase structures from Mycoplasma pneumoniae and Mycoplasma bovis were determined. An extra helix 7 is specific and conservatively found in almost all mycoplasma enolases, as confirmed by crystal structures and sequence alignment. Particular motifs for helix 7, which is composed of F-K/G-K-L/F-K-X-A-I, have been proposed and could be regarded as molecular markers. To our surprise, the genetic distances between any two mycoplasma enolases were obviously longer than those between the two corresponding species themselves, indicating divergent evolution of mycoplasma enolases, whereas no horizontal gene transfer was detected in mycoplasma enolase genens. Furthermore, different evolutionary patterns were adopted by different loop regions of mycoplasma enolase. Enolases from different Mycoplasma species also showed different affinities for PLG and FN. Our results indicate the rapid and divergent evolution of mycoplasma enolase and mycoplasmas. This study will also aid understanding the independent evolution of Mycoplasma species after separation from their common ancestor.